Pencegahan Kekerasan Seksual terhadap Anak Sekolah Dasar dan Sekolah Menengah Pertama di Kota Kendari - Raja Al Fath Widya Iswara; Elisa Rompas; Asrawati Azis; Indah Wulan Sari; Yosephin Siahaan; Baety Adhayati; Ida Bagus Putu Alit; Dudut Rustiyadi; Dwi Fitriyanti Arieza Putri; Liauw Djai Yen; C Andriyani; Geebert Dundu; Ria Kumala; Enno Elfandari; Sari Nur Indahty Purnamaningsih; Paula Lihawa (Penerbit Goodwood, 2026)
Purpose: This study evaluated the effectiveness of a structured educational intervention in improving knowledge, awareness, and preventive skills related to sexual violence among elementary and junior high school students in Kendari City. Research Methodology: A community-based program was conducted at the Kendari City Education and Culture Office involving 100 students. The intervention applied interactive and multimodal approaches, including lectures, educational videos, leaflets, role-play simulations, and group discussions. A quantitative pre-test and post-test design was used, along with participant satisfaction measured via a Likert scale. Data were analyzed descriptively. Results: Knowledge scores increased substantially from 64% (pre-test) to 95% (post-test). Participant satisfaction was very high, with 98% reporting positive responses. Students showed improved understanding of safe and unsafe touch, digital safety, and reporting mechanisms, alongside strong engagement during sessions. Conclusions: The intervention effectively enhanced knowledge and awareness of sexual violence prevention among school-aged children. Limitations: The study was limited by short-term evaluation and absence of long-term follow-up to assess sustained behavioral change. Contributions: This study provides an evidence-based and scalable model for school-based sexual violence prevention programs that can be adapted and implemented across elementary and junior high schools in other regions of Indonesia. The findings offer practical guidance for educators, healthcare professionals, and policymakers in developing interactive, child-centered prevention strategies to strengthen early awareness and reporting readiness among school-aged children.